COMPARATIVE STUDY OF THE OPINION OF THE STUDENTS INGRESSIONS AND EGRESSES OF THE COURSE OF PHYSICAL EDUCATION OF THE UNIVERSITY OF BRASILIA ON THE CURRICULUM OF PROFESSIONAL FORMATION (Fiep Bulletin - online, 2014)
The present study if it dedicates to the analysis of the quality of the course of Degree in Physical Education of the University of Brasilia. The comparison enters the opinion of ingressions and egresses allow to verify if its expectations had been taken care of, reformulated and/or extended, and, at the same time, to investigate the opinion on the important considered curricular experiences for the professional formation, supplying important subsidies the evaluation of the curriculum. The sample is composed of 186 students, being 81 ingressions, in the year of 2004, and 105 egresses between 1990 and 2004. The data had been analyzed by the Test of Qui-Square. The main conclusions: the difficulties of maintenance of the Brazilian public universities; the existing distance between the academic formation and the social reality, generating a without the relation between practical and theory; the criticism of egresses with the deepening of scientific knowledge and the formation to research. The university must, therefore, to review its curriculum and to provide to the egresses the access to a continued formation.
Keywords: Curriculum of Physical Education; professional formation; expectations